If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2x = c Solving 3 + -2x = c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = -3 + c Combine like terms: 3 + -3 = 0 0 + -2x = -3 + c -2x = -3 + c Divide each side by '-2'. x = 1.5 + -0.5c Simplifying x = 1.5 + -0.5c
| e-3.4x+1.5=2.5 | | 16t(8r+3v)= | | (3x+1.3)+(4x-3.8)=180 | | 13x+y=40 | | 7p+11=-5 | | x=5-y-9 | | 3x+5y=-26 | | -6-6x+7x=16 | | 5x-8x-11=-3x+4-11 | | -3(x+5)=2(10+x) | | 8n^2-16n-6=0 | | Y-2=8/9(x-9) | | 123+2h=927 | | 2(x+2)+7=6x-4(-2+x) | | 3x+10y=-10 | | 7x/26=12/59 | | 16cos^2x-1=0 | | 123+2h=937 | | 2x+31=-9 | | .8x-2.8=.4 | | ln(x^2)-ln(2*x)+1=0 | | -5(k+9)-(-2k-9)=-4k | | 2m-7=21-5m | | 9x-115+4x+27=107 | | (2*3.14*4*6.6)+(2*3.14*16)= | | 6x-8=5x+1 | | h(t)=-5t^2+30t+35 | | -2(4t-3)+6t=3t-6 | | (2*3.14*r*6.6)+(2*3.14*16)= | | 5y=3x+6x-2 | | -2x+20y=20 | | sinx=-0.2 |